P799 Perinatal factors and development of IBD: a national case–control study with nearly 50 years of follow-up: report from the epiIIRN database. (25th January 2019) - Velosa, M; Yerushalmi, B; Asayag, N; Focht, G; Navon, D; Hochner, H; Friedlander, Y; Brufman, I; Feldman, B; Balicer, R D; Cahan, A; Ledderman, N; et al.
Abstract: Background: The changing epidemiology of IBD suggests that environmental factors have a major role in inducing or modifying disease expression. Nevertheless, identifying modifiable environmental factors is challenging. We aimed to determine the association of very early-life exposure with the subsequent development of IBD in a unique cohort with a follow-up of nearly 50 years, by merging data from the Jerusalem Perinatal Study (JPS) and the epidemiology Israeli IBD Research Network (epiIIRN). Methods: We linked two relevant Israeli datasets: the epiIIRN and the JPS. The former is a validated registry of all IBD patients in the 4 national health maintenance organisations (HMOs), covering 98% of the population, and 1:3 age- and gender-matched non-IBD controls. The epiIIRN is updated to 01/2017. The JPS database recorded peri-natal information on a population-based cohort of 92, 408 births in 1964–76 and their parents. The linkage of these two datasets allowed us to identify IBD and non-IBD subjects from the JPS cohort and to analyse very early-life events potentially associated with the development of IBD. Assessment of demographic features was performed, with multi-variate analysis of caesarean section delivery, mother's age and birth weight. Results: A total of 465 individuals of the JPS cohort, born during 1964–1976, subsequently developed IBD (50.3% females, mean current age 47.9 ± 3.7 years, 53.5% with Crohn's disease (CD) and 46.5% with ulcerative colitis (UC). This translates into a prevalence rate of 5/1000 (or 0.5% of the population). The 1, 279 subjects without IBD identified within the JPS cohort were broadly similar to the cases (42.7% females, mean current age 47.8 ± 3.7 years). Mother's age at the time of delivery (17–34 years vs. ≥35 years) was not associated with a higher risk of developing IBD (95% confidence interval [CI] 0.80–1.57; p = 0.519; Fisher exact test). Delivery through caesarean section did not prove to be a statistically significant predictor of IBD diagnosis (95% confidence interval; p = 0.845; Fisher exact test) and birth weight, whether low (< 1499 g) or high (≥4500 g) was not associated with the development of IBD later in life (95% confidence interval; p = 0.779, Pearson's χ 2 test). Conclusions: The prevalence of IBD among the JPS cohort is comparable to the calculated national rate (0.5% of the population) which provides internal validity to this case–control study. We found that in this population very-early life factors such as mode of delivery (caesarean section), mother's age at birth and birth weight were not associated with a higher risk of developing IBD later in life, but further analysis using IBD subtype stratification (CD vs. UC) is warranted.